Knowledge, Attitudes, and Practices Concerning COVID-19 in Nepal - Bhattarai, Anil; Ranabhat, Kamal; Saud, Bhuvan; Bhattarai, Suraj; Paudel, Kiran; Acharya, Devaka Kumari; Tripathi, Sangita; Shah, Sangam; Bhatta, Nikita; Das, Santa Kumar (Journal of Nepal Health Research Council, 2023)
Background: Coronavirus disease-2019 (COVID-19) severely affects patients with chronic diseases. Adequate knowledge, attitudes, and practice related to COVID-19 is associated with decrease morbidity and mortality. Therefore, this aimed to assess knowledge, attitudes, and practice toward COVID-19 disease among chronic diseases patients visiting tertiary hospitals in Kathmandu. Methods: A cross-sectional study was conducted among chronic disease patients who visited Tribhuvan University Teaching Hospital and Manmohan Cardiothoracic Vascular and Transplant Center, Kathmandu. Structured questionnaire was used to collect patients’ socio-demographic data and perspectives on COVID-19. Results: Four hundred chronic disease patients participated in the study, with 53.2% female and 46.8% male, and 56.8% of age ?50 years. Overall, 55.5% of the participants had good knowledge, 56.2% had good practice, and 30.7% had positive attitude towards COVID-19. Younger patients, 18-34 years, were found to have higher odds of having good knowledge compared to other age groups (aOR: 2.5; 95% CI: 1.3-6.0). The patients with less than average family income and those unable to read and write had lower odds of having positive attitude towards COVID-19 (aOR: 0.6; 95% CI: 0.4-0.9 and aOR: 0.4; 95%CI: 0.2-0.9, respectively). A statistically significant correlation was found between the patients’ knowledge and practice, knowledge and attitude, and attitude and practice (p <0.001). Conclusions: Nearly half of the chronic disease patients in Nepal had poor knowledge and practice whereas more than two-third had negative attitude towards COVID-19 disease. Older age of the patient was significantly associated with poor knowledge and practice. Keywords: Attitudes; chronic diseases; COVID-19; knowledge; practice